Cholecystolithiasis and infection of the biliary tract with salmonella virchow: a very rare case in early childhood - Beiler, Hans Albert; Kuntz, Christian; Eckstein, T. M.; Daum, Roland (European journal of pediatric surgery, 1995)
Thieme E-Books & E-Journals